Cerebrolysin Ameliorates Focal Cerebral Ischemia Injury Through Neuroinflammatory Inhibition via CREB/PGC-1α Pathway - Guan, Xin; Wang, Yunjie; Kai, Guoyin; Zhao, Shunyi; Huang, Tingyu; Li, Youzhen; Xu, Yuan; Zhang, Luyong; Pang, Tao (Frontiers in Pharmacology, 2019)
Neuroinflammation is one of the important factors aggravating brain injury after ischemic stroke. We aimed to investigate the effects of cerebrolysin (CBL) on neuroinflammation in vivo and in vitro and the underlying mechanisms. The gene expressions of pro-inflammatory factors and anti-inflammatory factors were analyzed by real time PCR in rat transient middle cerebral artery occlusion (tMCAO) model, lipopolysaccharides-induced neuroinflammatory mice model and LPS-treated mouse primary microglia cells. The neuroprotective effects of CBL were evaluated by infarct size, Longa test and Rotarod test for long-term functional recovery in rats subjected to ischemia. The role of CREB/PGC-1α pathway in anti-neuroinflammatory effect of CBL was also determined by real time PCR and Western blotting. In the tMCAO model, administration of CBL at 3 h post-ischemia reduced infarct volume, promoted long-term functional recovery, decreased the gene expression of pro-inflammatory factors and increased the gene expression of anti-inflammatory factors. Correspondingly, in LPS-induced neuroinflammatory mice model, CBL treatment attenuated sickness behavior, decreased the gene expression of pro-inflammatory factors, and increased the gene expression of anti-inflammatory factors. In in vitro and in vivo experiments, CBL increased the protein expression levels of PGC-1α and phosphorylated CREB to play anti-inflammatory effect. Additionally, the application of the specific CREB inhibitor, 666-15 compound could effectively reverse the anti-inflammatory effect of CBL in primary mouse microglia cells and anti-ischemic brain injury of CBL in rats subjected to tMCAO. In conclusion, CBL ameliorated cerebral ischemia injury through reducing neuroinflammation partly via the activation of CREB/PGC-1α pathway and may play a therapeutic role as anti-neuroinflammatory agents in the brain disorders associated with neuroinflammation.